STRATEGI BUSINESS PLAN UNTUK MENGATASI MASALAH PEMASARAN DAN PRODUKTIVITAS IKM KAIN MOTIF JUMPUTAN KHAS YOGYAKARTA DALAM MEMAJUKAN INDUSTRI KREATIF DAERAH - Emmy Nurhayati; Elly Wuryaningtyas Yunitasari (Program Studi Teknik Industri, 2018)
Jumputan Motif Fabric is a type of fabric that resembles batik with special motifs and patterns. Sanggar Maharani which is engaged in the fabric industry has problems in productivity and marketing. Objective Matrix (OMAX) and Business Model Canvas (BMC) methods can be applied to overcome these problems.The purpose of this study is on the production floor of Sanggar JumputanMaharani and develop motives business strategies to be able to compete in the market. The specific target of this study is to obtain a business plan to deal with competition and obtain increased productivity on the production floor. This research also plays a major role in advancing the creative industry and preserving the culture of the city through Yogyakarta.The results are performance standards values ​​for efficient use of labor 19,7801 units / person, minimization of defective products 0.0055%, absence 0.0018%. The calculation results with the Objective Matrix model on the production floor of Sanggar Jumputan Maharani found that the highest value of performance is 258.24. The results of the productivity index that shows the lowest productivity index is in April 2018 which is equal to -23.40% and the highest productivity index is in March 2018 which is 45.06%. While the right business planning strategy for the Sanggar Jumputan Maharani, which consists of 9 blocks: Customer Segments, Value Propositions, Channels, Customer Relations, Revenues Streams, Key Resources, Key Activities, Key Partnerships, and the Cost Structure shown in the Business Model Canvas Template.